The Role of HR in the Transforming Workplace Challenges, Technology, and Future Directions - Pandey, Anamika (Productivity Press, 2024)
Changing technology and the growing demand for workforce intelligence have ushered in a new era of HR transformation and have compelled HR professionals to continually ideate, innovate, and adapt. This book covers the changing role of HR in the transformation of workplaces to be successful globally.
Description based on print version record
Keywords: Personnel departments -- Employees; Personnel management; Organizational change; Services du personnel; Personnel; Personnel; Direction; Changement organisationnel